A Simple LMS Algorithm Based Smart Antenna to Solve the Reader Collision Problems in RFID System - Sayeed, M.S.I.; Young Soo Kim (2009 International Conference on Information and Multimedia Technology, 2009)
Radio Frequency Identification (RFID), a prominent technology which carries information by radio waves, evolving rapidly as a major and innovative way to meet the growing demand for more powerful, cost-effective and highly efficient technology to wirelessly identify and track goods and assets worldwide. To improve the coverage, read rate and accuracy of this highly prospective technology dense reader RFID systems should be employed where reader collisions are very likely to happen. Reader collision problems are the main constraints to large-scale deployment of the multi-reader RFID systems and the ability to handle this problem efficiently is crucial for the performance, speed, efficiency and reliability of the whole system. In this paper we proposed a simple LMS algorithm based smart antenna technique to solve the reader collision problems efficiently in a dense reader environment. The simulation results show that, the proposed method will be a great approach to solve this problem due to the characteristics such as robustness and implementation simplicity.